Implementation of Coloring and Puzzle Play Therapy to Reduce Hospitalization Anxiety in Preschoolers: A Case Study - Diah Ayu Agustin; Shofiyyul Izhan; Ika Melasari; Bambang Sucipto (Persatuan Perawat Nasional Indonesia (JPPNI), 2026)
Deterioration in physical condition, environmental changes, medical treatment, loss of control over activities can cause anxiety in preschool children hospitalized with bronchopneumonia. The aim of the study: to determine the results of the application of puzzle and coloring therapy in 2 children who experienced anxiety during hospitalization. Method: Descriptive case study. Coloring therapy in patient 1 (N) and puzzle therapy in patient 2 (A) was carried out once a day for 30 minutes, for three days of treatment. Anxiety was measured before and after therapy using a questionnaire based on the Facial Image Scale (FIS). Results: Coloring therapy is effective in reducing anxiety levels from very severe to moderate. Puzzle therapy is also proven to be effective in reducing anxiety levels from severe to mild. Conclusion: Nurses play a crucial role as care providers, educators, and collaborators in applying puzzle and coloring therapy to reduce anxiety in hospitalized preschool children through appropriate play spaces and materials, accompanying the child, monitoring responses after play, and collaborating with parents and healthcare team members.